2022
DOI: 10.1038/s41598-022-18008-y
|View full text |Cite
|
Sign up to set email alerts
|

Temperature gradient sensing mechanism using liquid crystal droplets with 0.1-mK-level detection accuracy and high spatial resolution

Abstract: We proposed the detection mechanism of the micro-levels of temperature gradient in a micro-electromechanical system using the unidirectional rotation of cholesteric-liquid crystal (Ch-LC) droplets. Ch-LC droplets in the presence of an isotropic phase subjected to a heat flux rotate with a speed proportional to the magnitude of the temperature gradient. We further quantified the temperature gradient-to-torque conversion efficiency to apply the thermomechanical cross-correlation to the detection of temperature g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…[29][30][31] It is, however, difficult to extract information about the analyte identity purely from the final texture of a nematic LC, save a few exceptions: for example, recent work has shown that specific information about the volatile compounds that are being sensed can be extracted based on the dynamics of the LC response 9,32 or by attaching specific antibodies to the interface. 26 CLCs and CLC-derived materials, however, can instead show gradients of response on their own 11,17,[33][34][35][36] owing to distortions induced in the helical structure that change the reflected color. These color changes are potentially more amenable to eventual sensing applications without targeting specific molecules, often able to be read out by the unaided eye 33,35 and without the traditional crossed polarizer set-ups necessary with nematic LC materials.…”
Section: Introductionmentioning
confidence: 99%
“…[29][30][31] It is, however, difficult to extract information about the analyte identity purely from the final texture of a nematic LC, save a few exceptions: for example, recent work has shown that specific information about the volatile compounds that are being sensed can be extracted based on the dynamics of the LC response 9,32 or by attaching specific antibodies to the interface. 26 CLCs and CLC-derived materials, however, can instead show gradients of response on their own 11,17,[33][34][35][36] owing to distortions induced in the helical structure that change the reflected color. These color changes are potentially more amenable to eventual sensing applications without targeting specific molecules, often able to be read out by the unaided eye 33,35 and without the traditional crossed polarizer set-ups necessary with nematic LC materials.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9] Many of the same characteristics of LCs that make them amenable to use in displays (high responsiveness to external stimuli and optical feedback) can be applied in sensing technology to provide clear, rapid feedback about a system. Classically used for temperature sensing applications, [10][11][12][13][14] LCs have more recently found use in detecting the presence or absence of amphiphiles [3] or harmful volatile compounds [5,7,[15][16][17] that can contaminate a system. Most reported sensing applications use nematic liquid crystals (NLCs), ordered fluid phases that often function based on a change of the LC alignment [2,18,19] or loss of the LC phase altogether.…”
Section: Introductionmentioning
confidence: 99%
“…To directly detect chirality in solution, the VCSP of liquid crystal micro-droplets (LCμDs) can serve as a novel chirality sensing mechanism. We have recently reported that cholesteric liquid crystals (LCs) are responsive to external stimuli such as light [13], electric fields [14], and heat flux [15][16][17][18]. Achiral nematic LCs, composed of rod-like molecules with their long axes aligned along a specific direction at equilibrium, exhibit spontaneous twisting of the director along an axis when doped with chiral compounds [19].…”
Section: Introductionmentioning
confidence: 99%